Experimental Study on Shear Failure Mechanism and the Identification of Strength Characteristics of the Soil-Rock Mixture - Shaorui Sun; Feng Zhu; Jihong Wei; Wuchao Wang; Huilin Le (Shock and Vibration)
Soil-rock mixture (SRM) is a special geological material that has the unique properties of rock or soil. Studies on the strength characteristics of the SRM have very important theoretical significance and practical value. In this study, the gravel proportions, gravel sizes, gravel shapes, and repetitive results of shear experiments are considered in laboratory experiments and for the identification of strength parameters. To the gravel shapes, from the angle of the composition materials of SRM, the experimental samples include samples with breccia gravels and with subrounded gravels. And, in this study, the laboratory model experiment is used to research the strength characteristics of SRM. In addition, the shear failure mechanism is used to establish the relationship between the microfailure mechanism and the macrostrength parameters identification. Taking gravel proportion, gravel size, gravel shape, and repetitive shear process as the influencing factors of the SRM, the laboratory models have been remolded, and laboratory direct shear experiments have been carried out. The shear deformation laws of the SRM are researched on the basis of the analysis of the curves of shear stress and the horizontal displacement.